Transition from ferromagnetism to superparamagnetism in diluted magnetic Fe(II)-doped ZnSe microspheres - Li, Tingting; Wang, Wenhe; Shi, Quan; Zhang, Jian; Zhao, Lijuan (Journal of magnetism and magnetic materials, 2022)
•Room-temperature ferromagnetism was observed in Fe2+-doped ZnSe microspheres.•Transition from ferromagnetism to superparamagnetism was observed in doped samples.•The transition temperature increases with the increase of doping concentration. Iron (Fe) doped ZnSe (ZnSe:Fe) microspheres with different doping concentration were prepared by simple solvothermal process. XRD, Raman scattering and SEM results indicated that doping of Fe ions does not change the structure and morphology of ZnSe host. The increase of a-axis lattice parameters and redshift of Raman peaks confirmed the successful incorporation of Fe ions, and XPS results showed that the doped iron is in Fe2+ state. ICP-AES results revealed that the real concentration of Fe incorporated into ZnSe lattice was much lower than the original doping concentration, which is possibly subject to the low solubility of Fe ions in ZnSe host lattice. Optical characterizations showed that increasing Fe concentration would lead to more defects in the host lattice. The magnetic characterizations of ZnSe:Fe microspheres reveal transition from ferromagnetism to superparamagnetism. The transition temperature increases as the increase of doping concentration. Further, these microspheres show a weak room-temperature ferromagnetic exchange interaction was observed by field-dependent magnetization. No evidence of diamagnetism or spin glass state was found in Fe-doped ZnSe microspheres. Due to the lower doping concentration, the dopants could not be expected to cluster or to form inclusions, therefore the observed magnetic behavior is believed to be arising from the random substitution of Fe ions and their magnetic exchange interaction with the delocalized carriers in the ZnSe host.